1958
DOI: 10.1126/science.128.3331.1090-a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium and Vitamin E on White Muscle Disease

Abstract: bar of osmotic pressure were, respectively, 0.576 +0.004, 0.570+0.004, 0.568 +0.004, and 0.562 ? 0.005. These sensitivity values for the separate couples are averages for determinations at five osniotic pressures. The standard errors measure the accuracy of proportionality between output, in microvolts, and osmotic pressure. The coefficient of variability of the voltage readings for five replicates of each of the KCl concentrations was determined for each of the thermocouples; the over-all average of these 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Table I shows that, within certain limits, decreases in amount of Ea used in the subcutaneous eliciting injection led to increases in survival time. This prolongation of syndrome was analogous to the effect due to increasing amounts of antibody described in our previous studies on acute and protracted anaphylactic shock (2,3). …”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Table I shows that, within certain limits, decreases in amount of Ea used in the subcutaneous eliciting injection led to increases in survival time. This prolongation of syndrome was analogous to the effect due to increasing amounts of antibody described in our previous studies on acute and protracted anaphylactic shock (2,3). …”
Section: Resultssupporting
confidence: 82%
“…It was previously reported from this laboratory that in actively or passively sensitized guinea-pigs, lethal anaphylactic shock could be regularly elicited by injection of the homologous antigen via the subcutaneous route (1,2,3). The anaphylactic shock was of an acute or protracted type and within certain limits the degree of prolongation of the anaphylactic shock was proportional to the amount of antibody in the circulation at the time of challenge (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Later work in this country and in New Zealand (5,21,27) showed that as little as 0.1 p.p.m. of Se was effective in preventing white muscle disease in lambs and calves.…”
Section: Seleniummentioning
confidence: 95%
“…Experimental evidence that complement plays a significant role in the pathogenesis of interstitial inflammatory reactions in the lung is considerable [40][41][42][43][44][45][46][47], In models of acute lung disease, a direct correlation has been demonstrated between the extent of in jury and the complement-fixing activity of preformed immune complexes infused intrabronchially into experimental animals [48][49][50]. Histologic examination of these animals shows a diffuse, confluent hemorrhagic reac tion in the alveolar spaces, vessel walls and interstitia of the lungs with the neutrophil as the predominant infiltrating cell type.…”
Section: Actions Of the Anaphylatoxins In Vivomentioning
confidence: 99%